Diversification in Indian Agriculture toward High‐Value Crops: The Role of Small Farmers. (14th June 2012) - Birthal, Pratap Singh; Joshi, Pramod Kumar; Roy, Devesh; Thorat, Amit
<x xml:space="preserve">Abstract</x> Diversification by small farmers toward high‐value crops (fruits and vegetables [F & V]) that can raise farm incomes significantly has always been in question because of several reasons such as diseconomies of scale and lack of access to inputs such as capital and information. We present evidence that in India diversification toward high‐value crops exhibits a pro‐smallholder (rather than anti‐smallholder) bias. The smallholders however play a proportionally larger role in vegetables than in fruits cultivation. These patterns are consistent with simple comparative advantage‐based production choices. Even with small landholdings if labor endowments are high, such farmers diversify toward F & V. Though fruits cultivation is also labor intensive relative to cereals, it is less so relative to vegetables. Greater capital intensity implies a comparatively important role of credit in fruits. The results are robust to several tests on specification including those related to self‐selection. Chez les petits exploitants agricoles, la diversification en faveur de cultures à valeur élevée (fruits et légumes) permettant d'accroître considérablement le revenu agricole a toujours été remise en question pour diverses raisons, notamment les déséconomies d'échelle et le manque d'accès aux intrants comme le capital et l'information. Dans le présent article, nous montrons qu'en Inde, la diversification en faveur de cultures à valeur élevée semble plutôt favorable que défavorable aux petits exploitants agricoles. Toutefois, les petits exploitants sont proportionnellement plus présents dans la culture maraîchère que dans la culture fruitière. Ces observations concordent avec les choix d'une production fondée sur les avantages comparatifs. Même dans le cas des petites exploitations, lorsque les besoins de main‐d'œuvre sont élevés, elles se tournent vers les cultures fruitière et maraîchère. Bien que la culture fruitière soit une activitéà forte intensité de main‐d'œuvre comparativement à la culture céréalière, elle l'est moins que la culture maraîchère. L'intensité de capital élevée de la culture fruitière signifie que le crédit joue aussi un rôle important. Les résultats de plusieurs tests de spécification sont robustes, y compris ceux liés à l'auto‐sélection.